PHYSIC NUT (JATROPHA CURCAS L.) DISEASES IN LAMPUNG PROVINCE - CIPTA GINTING (BIOTROPIA, 2009)
Intensified cultivation of physic nut (Jatropha curcas L.) could raise the importance of plant diseases.  The objectives of this research were to diagnose diseases occurring on physic nut in Lampung Province and to determine their intensity.  Field observation was conducted in four districts: South Lampung, Tanggamus, Bandarlampung, and Tulang Bawang.  Disease intensity, whether expressed as disease incidence or severity, was recorded from plant samples determined by making diagonal lines across the field on which five observation spots were made.  On each spot, five plant samples were observed.  Specimens were also collected and placed individually in plastic bags for laboratory observation.  The diseases found on physic nut in Lampung Province were cercospora leaf spot, alternaria leaf spot, fusarium wilt, and bacterial wilt.  In addition, leaf malformation first thought to be viral disease was commonly found in many locations.  Further mechanical transmission failed to produce similar symptom on tested plants and higher population of mites were found on malformed leaves than that in normal leaves.  Based on the disease distribution and intensity, the most likely threatening disease in physic nut cultivation is bacterial wilt.  Fusarium also  caused wilt, but it was only found in one subdistrict with low incidence.  Keywords: Alternaria, Cercospora, fusarium wilt, bacterial wilt, Jatropha curcas diseases